Proposta de melhoria na utilização do indicador de eficiência global do equipamento (OEE) de uma linha automática de pincéis imobiliários - Grando, Laila (2017)
With the expansion of market competitiveness, companies are seeking to increase the efficiency of their processes as a new strategy for their business. For this, one of the philosophies used is Total Productive Maintenance (TPM), which it presents a measure called Overall Equipment Effectiveness (OEE) as the main function to identify improvements in the equipment efficiency. Thus, this work found to analyze the results of the use of OEE in an automatic line of paint brushes in a big company, and to propose improvements for a better use of the tool. Thus, through the variables of performance, availability and quality, data were collected from software called Alpha provided by the company. With the analyzes carried out from February to August 2017, an increase in efficiency of 20.29% and a 29.9% productivity of the equipment were identified after some specific improvements implemented, evidencing the benefits of applying this measure. Therefore, after the analyzes were suggested measures of improvement of the system and its use so that the company can achieve its objective.